Obstacles to Labour Market Participation among Arab Women in Israel - Sami H. Miaari; Nabil Khattab; Maha Sabbah-Karkabi (Institute of Labor Economics (IZA), 2020)
This study investigates the factors that underlay the low labour force participation rate among Palestinian-Arab women in Israel relative to Jewish women despite the high educational attainment among this group. We focus on four factors that could explain this pattern: (i) socioeconomic factors such as age and education, (ii) culture factors such as the religiosity of the individual-woman and her family, (iii) family structure and related public policies, and (iv) the early retirement of Arab women from the labour market. We find that all four of these factors affect the probability of Palestinian-Arab women participating in the labour market. We conclude by discussing the implications of our findings for labour market policies.
Keywords: J01; J15; J13; J18; J26; 330; labour market participation; Arab women; public policy; gender; nationality; religiosity; early retirement